Liberalism and mitochondrial replacement technique - Tang, Marco (Journal of medical ethics, 2025)
How should defenders of liberalism think about access to reproductive technologies? Mitochondrial replacement technique (MRT) enables women with pathogenic variations of mitochondrial disease to have children without the fear of transmission. This technology can also allow lesbians, or partners with female - assigned physiology (PFP), to have genetically related offspring. Cavaliere and Palacios-Gonzalez argue that lesbians should be able to access MRT on autonomy grounds. They argue MRT should not be restricted to those with mitochondrial disease because it is non-therapeutic and invokes the Millian harm principle. Yet, Baylis argues that a desire for genetically related offspring is not sufficient to access MRT because it contributes to harmful social narratives about adopted families. I strengthen Cavaliere and Palacios-Gonzalez's liberal defence by bringing another liberal commitment-equality. Ultimately, I argue that the liberal state must allow PFPs to use MRT. I first show that the use of MRT by PFPs is permissible even if MRT is therapeutic by comparing MRT with cosmetic surgery - that is, social uses of therapeutic interventions are permitted if we are interested in doing so. Borrowing from Dillard, a possible interest is self-replication. Next, I outline and respond to a possible criticism by Baylis - MRT is necessary but not sufficient for self-replication. Ultimately, I show that the liberal state must permit MRT because (a) it provides PFPs with an equal opportunity to experience having genetically related offspring with their partner and (b) contributing to harmful social narratives is insufficient for limiting autonomy.